Change Management In The Selected Automobile Companies In Tamilnadu – Focusing On Awareness Of Employees (The Review of Diabetic Studies, 2025)
In the contemporary business environment, change has become inevitable for organizations seeking to remain competitive, particularly in the automobile industry where rapid technological advancements, automation, and market dynamics continuously reshape organizational processes. The success of change initiatives largely depends on employees’ awareness and understanding of change management practices. The study examines the level of awareness of employees regarding change management practices in selected automobile companies in Tamil Nadu. The study adopted a descriptive and analytical research design based mainly on primary data collected from 479 employees working in passenger vehicle, commercial vehicle, and two-wheeler manufacturing companies in Tamilnadu through a structured questionnaire. The tools of Descriptive statistics, Cronbach’s Alpha, Factor analysis, Mann–Whitney U test, and Kruskal–Wallis test, were employed to analyze the data. The findings reveal that the overall awareness level of employees towards change management practices is moderate. Employees generally recognize the need for organizational change; however, relatively lower awareness is observed in areas related to communication, counselling, and training. The study further identifies significant differences in awareness levels across several demographic, job-related, and organizational variables. Factors such as gender, age, education, income, nature of employment, experience, job level, participation in decision making, type and frequency of changes, workload, and perceived job security significantly influence employees’ awareness of change management. In contrast, marital status, family type, family size, residential place, and type of automobile company do not show significant differences.